Numerical Model of Surface and Quasi-Spherical Sea Noise and Its Application to Analysis of DIFAR Systems - RUDNICKI, Mariusz; SALAMON, Roman; MARSZAL, Jacek (Archives of Acoustics, 2021)
Various types of passive sonar systems are used to detect submarines. These activities are complex and demanding. Therefore, computer simulations are most often used at the design stage of these systems. For this reason, it is also necessary to simulate the acoustic ambient noise of the sea. The article proposes a new numerical model of surface and quasi-spherical sea noise and presents its statistical parameters. The results of the application of the developed noise model to analyse the received signals of the DIFAR sonobuoy are also presented.